RPCM: a strategy to perform reliability analysis using polynomial chaos and resampling: Application to fatigue design - Notin, Alban; Gayton, Nicolas; Dulong, Jean Luc; Lemaire, Maurice; Villon, Pierre; Jaffal, Haidar (European Journal of Computational Mechanics, 2010)
Using stochastic finite elements, the response quantity can be written as a series expansion which allows an approximation of the limit state function. For computational purpose, the series must be truncated in order to retain only a finite number of terms. In the context of reliability analysis, we propose a new approach coupling polynomial chaos expansions and confidence intervals on the generalized reliability index as truncating criterion.